PENGARUH RASIO PROFITABILITAS TERHADAP NILAI PERUSAHAAN-PERUSAHAAN KELUARGA DI INDUSTRI RITEL - Hary Saputra Sundoro (Jurnal Manajemen, 2019)
The purpose of this research is to determine the effect of EPS, ROA, and ROE on changes in the value of family retail companies. In addition, this research is also expected to be able to answer the magnitude of the influence of profitability ratios on changes in the value of retail companies. The research method used is panel regression analysis which then the model used is Fixed Effect Model (FEM). The results of this research show that only EPS can be used as a variable on the value of retail companies. Then profitability ratios can influence the value of retail companies but not the most dominant ones.